2023
DOI: 10.1186/s12951-023-02098-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic mesenchymal stem cell-derived exosomes promote the survival of skin flaps after ischaemia–reperfusion injury via mTOR/ULK1/FUNDC1 pathways

Chao Deng,
Kangkang Dong,
Yongjun Liu
et al.

Abstract: Flap necrosis, the most prevalent postoperative complication of reconstructive surgery, is significantly associated with ischaemia–reperfusion injury. Recent research indicates that exosomes derived from bone marrow mesenchymal stem cells (BMSCs) hold potential therapeutic applications in several diseases. Traditionally, BMSCs are cultured under normoxic conditions, a setting that diverges from their physiological hypoxic environment in vivo. Consequently, we propose a method involving the hypoxic precondition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that preconditioning MSCs with various physical and chemical stimuli, such as hypoxia and lipopolysaccharide (LPS), might enhance the therapeutic effects of the corresponding MSC-Exos [ 15 , 16 ]. However, these harmful stimuli may also negatively affect cell vitality and proliferation, leading to cell senescence and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that preconditioning MSCs with various physical and chemical stimuli, such as hypoxia and lipopolysaccharide (LPS), might enhance the therapeutic effects of the corresponding MSC-Exos [ 15 , 16 ]. However, these harmful stimuli may also negatively affect cell vitality and proliferation, leading to cell senescence and differentiation.…”
Section: Introductionmentioning
confidence: 99%